Endothelial Lactate Controls Muscle Regeneration from Ischemia by Inducing M2-like Macrophage Polarization - Zhang, Jing; Muri, Jonathan; Fitzgerald, Gillian; Gorski, Tatiane; Gianni-Barrera, Roberto; Masschelein, Evi; D’Hulst, Gommaar; Gilardoni, Paola; Turiel, Guillermo; Fan, Zheng; Wang, TongTong; Planque, Mélanie; et al. (Cell metabolism, 2020)
Endothelial cell (EC)-derived signals contribute to organ regeneration, but angiocrine metabolic communication is not described. We found that EC-specific loss of the glycolytic regulator pfkfb3 reduced ischemic hindlimb revascularization and impaired muscle regeneration. This was caused by the reduced ability of macrophages to adopt a proangiogenic and proregenerative M2-like phenotype. Mechanistically, loss of pfkfb3 reduced lactate secretion by ECs and lowered lactate levels in the ischemic muscle. Addition of lactate to pfkfb3-deficient ECs restored M2-like polarization in an MCT1-dependent fashion. Lactate shuttling by ECs enabled macrophages to promote proliferation and fusion of muscle progenitors. Moreover, VEGF production by lactate-polarized macrophages was increased, resulting in a positive feedback loop that further stimulated angiogenesis. Finally, increasing lactate levels during ischemia rescued macrophage polarization and improved muscle reperfusion and regeneration, whereas macrophage-specific mct1 deletion prevented M2-like polarization. In summary, ECs exploit glycolysis for angiocrine lactate shuttling to steer muscle regeneration from ischemia. [Display omitted] •Endothelial loss of pfkfb3 impairs ischemic muscle revascularization and regeneration•EC-derived lactate instructs MCT1-dependent macrophage functional polarization•Lactate-polarized macrophages promote muscle revascularization and regeneration•Restoring lactate levels improves macrophage polarization and recovery from ischemia Endothelial cells (ECs) critically control muscle recovery from ischemia by secreting lactate. Angiocrine lactate is taken up and oxidized by macrophages in an MCT1-dependent fashion. Lactate-mediated macrophage polarization promotes revascularization and muscle regeneration. Consequently, EC-specific loss of pfkfb3 lowers muscle lactate levels and impairs muscle recovery from ischemia.